Perspectivas para a aplicação da tecnologia BECCS para a captura de CO2 na indústria de papel e celulose no Brasil - Borges, Caroline de Barros (Universidade Federal de São Carlos, 2020)
Pulp and paper production in Brazil has maintained a marked growth in recent years, as a result of favorable climate conditions for a high productivity of eucalyptus and the consolidation of the country as a major exporter of pulp. In the global ranking, Brazil is the eighth largest producer of paper and the second largest producer of pulp, behind only of the United States. The pulp and paper industry is considered to be one of the largest consumers of energy, however, it stands out as one of the few Brazilian sectors that generates most of the energy consumed in its own process. Companies in the sector use by-products from their processes to generate thermal and electric energy, especially black liquor, which comes from the pulp process. Fuel combustion to generate heat and steam used in the process is identified as the main source of the greenhouse gas emissions in this industry, being responsible for about 3% of the emissions in the entire industrial sector. In this context of large scale emissions, the pulp and paper segment fulfills the requirements for the implementation of CO2 capture and storage from the application of the technological model called BECCS (Bio-Energy with Carbon Capture and Storage), which may be able to reduce the greenhouse gas emissions, being recognized as an important solution for globally mitigating the emissions. In the described context, this undergraduate study aims to assess the amount of CO2 emitted in pulp and paper mills in Brazil and the impact on the emissions through the application of the BECCS model. The study provides an overview of the current development of this technology, detailing methods of capture, transport, and storage, as well as CO2 capture techniques applied to the pulp and paper sector. From a case study, CO2 emissions were obtained in a typical pulp mill in Brazil and the potential for CO2 removal was estimated through a capture system in the chemical recovery boiler. The implementation of BECCS technologies in the Brazilian pulp and paper sector showed a high potential for negative emissions and the prospect of intensifying the use of these processes depends not only on the development of technologies, but also on a higher government incentive that could make the practice economically feasible.
Expectations for the application of the BECCS technology to CO2 capture in the cellulose & paper industries
Keywords: Papel e Cellulose; Emissões; Bioenergia; Captura e Armazenamento CO2; Tecnologia BECCS; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::PAPEL E CELULOSE